Endothelium and autoimmunity - Meroni, Pier Luigi (Henry Stewart Talks, 2007)
Physiological functions of the endothelium, Endothelium as a target and player of immune responses, Endothelium in autoimmune vasculitis and vasculopathies, Anti-endothelial cell antibodies, Anti-phospholipid syndrome, Scleroderma, Markers of endothelial perturbation